Copper/Palladium Synergistic Catalysis for the syn‐ and anti‐Selective Carboboration of Alkenes1. (27th February 2015) - Logan, Kaitlyn M.; Smith, Kevin B.; Brown, M. Kevin
Abstract A method for the diastereoselective carboboration of 1, 2‐disubstituted styrenes with aryl/vinyl bromides and (Bpin)2 is reported. High diastereoselectivities and yields are observed for the formation of either diastereomer of the product from a single alkene isomer. These reactions provide access to a diverse range of structures from simple starting materials.